Front Cover: Reductive Cleavage Method for Quantitation of Monolignols and Low‐Abundance Monolignol Conjugates (ChemSusChem 10/2018). Issue 10 (14th May 2018) - Regner, Matt; Bartuce, Allison; Padmakshan, Dharshana; Ralph, John; Karlen, Steven D.
Abstract : The Front Cover shows how the derivatization followed by reductive cleavage (DFRC) lignin characterization assay fragments lignins into small monomeric components. Unlike other lignin degradation assays (e.g., thioacidolysis and nitrobenzene oxidation), the DFRC assay cleaves β‐aryl ethers without hydrolyzing the γ‐esters present in some lignin, especially grass lignin. This robust method works well on whole biomass, as well as lignins isolated from softwoods, hardwoods, and grasses. We have optimized each step of the DFRC method to provide highly accurate quantitative data for both the traditional monolignols (i.e., H, G, and S) and the less‐abundant γ‐ester‐containing monolignol conjugates. More information can be found in the Communication by Regner et al. onpage 1600 in Issue 10, 2018 (DOI:10.1002/cssc.201800617 ).